Characteristics of Biocompatible Coatings on Dental Implants - Alexei Yumashev (Journal of Global Pharma Technology, 2016)
The purpose of this article is to give an overview of various biocompatible modifications of the implant surface and factors that mainly affect processes at the implant-bone interface. This review summarizes and explains the factors that are currently recognized as important for dental implants osseointegration: body materials and coatings, topography, hydrophilicity and polarity of the implant surface. Implant body materials (titanium, zirconium) are designed to provide mechanical stability. Their effect on bone cells can be improved with the help of surface treatment with various materials that include calcium phosphates, strontium, bio-glass, and diamond-like carbon. Surface topography can be changed using various methods, for example, plasma spraying, sandblasting, acid etching and microarc oxidation to increase bone contact with the implant. The hydrophilicity and polarity of the surface of the implants shows a significant cell adhesion effect. At the present time the currently used dental implant materials are showing satisfactory clinical results, ongoing research on innovative surfaces is necessary to improve and accelerate the of dental implant osseointegration.Keywords: Dental implants, Implant body materials, Biocompatible coatings, Osseointegration.